Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1128/aac.03925-14
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Attenuates Colistin-Induced Nephrotoxicity in Mice via Activation of the Nrf2/HO-1 Pathway

Abstract: bNephrotoxicity is the major dose-limiting factor for the clinical use of colistin against multidrug-resistant (MDR) Gram-negative bacteria. This study aimed to investigate the protective effect of lycopene on colistin-induced nephrotoxicity in a mouse model. Fifty mice were randomly divided into 5 groups: the control group (saline solution), the lycopene group (20 mg/kg of body weight/day administered orally), the colistin group (15 mg/kg/day administered intravenously), the colistin (15 mg/kg/day) plus lycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 73 publications
(114 reference statements)
5
85
0
1
Order By: Relevance
“…This indicates colistin treatment decreases the neurons capacity to breakdown superoxide anions and hydroxyl radicals; further exacerbating ROS mediated oxidative stress. Coincidently, we have previously demonstrated that the co-administration of antioxidants such as lycopene have been shown to be protective against polymyxin-induced nephrotoxicity in mice[35]. This supports the notion that oxidative stress pathways play an important role in polymyxin-induced neuro-cytotoxicity.…”
Section: Discussionsupporting
confidence: 74%
“…This indicates colistin treatment decreases the neurons capacity to breakdown superoxide anions and hydroxyl radicals; further exacerbating ROS mediated oxidative stress. Coincidently, we have previously demonstrated that the co-administration of antioxidants such as lycopene have been shown to be protective against polymyxin-induced nephrotoxicity in mice[35]. This supports the notion that oxidative stress pathways play an important role in polymyxin-induced neuro-cytotoxicity.…”
Section: Discussionsupporting
confidence: 74%
“…Mitochondria and ER form structural and functional networks essential for maintenance of cellular homeostasis and determine the cell fate under various pathophysiological conditions, including oxidative stress (31). This correlates with the current literature evidence that both the ER and mitochondrial pathways are involved in polymyxin-induced nephrotoxicity (16,30,32). Recently, it was reported that activation of the death receptor and mitochondrial pathways is involved in polymyxin-induced apoptosis in NRK-52E cells (15,30).…”
Section: Discussionsupporting
confidence: 68%
“…Nephrotoxicity is usually reversible but can sometimes result in chronic kidney disease (CKD) [6]. Oxidative stress plays an important role in the pathogenesis of COL-induced nephrotoxicity so the protective effects of antioxidative agents, such as ascorbic acid, lycopene, and N-acetylcysteine [NAC] have been investigated recently [2,7,8]. NAC is commonly used as a mucolytic agent, but it has powerful anti-inflammatory and antioxidant activities [9].…”
Section: Introductionmentioning
confidence: 99%